Deskripsi Gejala dan Tingkat Serangan Penyakit Bercak pada Batang Tanaman Buah Naga Merah (Hylocereus polyrhizus, L.) di Padang Pariaman, Sumatera Barat - Yuni Syafnidarti; Nasril Nasir; - Jumjunidang (Universitas Andalas, 2013)
Study of symptom and disease severity of stem spotting disease on red dragon fruit (Hylocereus polyrhizus, L.) was conducted from December 2012 to February 2013 in Padang Pariaman, West Sumatera. Laboratory and screen house work were carried out at Solok Tropical Fruit Research Institute and microbiology laboratory of Biology Department at Faculty of Mathematics and Natural Science, Andalas University, Padang. This study used direct observation method and the data was analyzed descriptively. Objectives of the research were to characterize and identify the causes of stem spotting disease symptom and then to measure disease incidence in production centers of dragon fruit in Padang Pariaman, West Sumatra. The result showed that percentage of stem spotting disease of dragon fruit was 99,5% while disease severity index of it was 2,2 (moderate severity). Disease symptoms were spotting/patches of brown to black round surrounded by yellow halo. The pathogen was identified as Colletotrichum gloeosporoides. Keywords: Dragon fruit, stem spotting, identification